STUDY OF SALMONELLA CONTAMINATION IN QUAIL SHELL EGGS SOLD IN SELECTED MARKETS OF BAMAKO - Brahima Sacko; Modibo Diakité; Chaka Traore; Amadou Sery; Alou Sanogo; Kadiatou Coulibaly (World Journal of Biology Pharmacy and Health Sciences, 2026)
In Mali, poultry farming constitutes one of the valuable sources of income for populations. With enormous production potential, essential conditions to achieve quality and health safety of poultry products in general, and quail eggs in particular, must be established. This study, conducted between January and May 2018, aimed to evaluate the contamination of quail eggs sold in selected markets of Bamako. It involved 104 egg samples collected from four (04) markets in Bamako. The various samples were inoculated first in a pre-enrichment medium (buffered peptone water free of indole), then into enrichment media (tetrathionate broth and Rappaport-Vassiliadis broth), followed by bacterial isolation on selective media (Salmonella-Shigella agar, MacConkey agar) and identification through biochemical tests and API strips. The work yielded an overall Salmonella prevalence of 5.76%, which varied according to sampling sites.